1992
DOI: 10.5006/1.3315879
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Kinetics of Low- and High-Alloy Steels in Chlorine-Containing Gas Atmospheres

Abstract: combustion and coal gasification, waste incinerators, fossil-fuel-fired boilers, and gas turbines is hightemperature corrosion. Most materials, when exposed at high temperatures to aggressive gaseous compounds, such as hydrogen sulfide, oxygen and hydrogen chloride or chlorine, are rapidly attacked. 1-3 Less information exists considering the performance of materials in coal gasification atmospheres containing small amounts of hydrogen chloride gas or chlorine.Additional corrosion problems have been associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 12 publications
2
16
0
2
Order By: Relevance
“…(2) and (3), the fracture toughness of both the film and the film/substrate interface increases with increasing deposition temperature and reducing film thickness. This corresponds well with earlier results [36], where the alumina films delaminate from the substrate after reaching a critical thickness. Owing to an increased thickness, the stress near the interface increases, resulting in a lower fracture toughness of the film/substrate interface.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(2) and (3), the fracture toughness of both the film and the film/substrate interface increases with increasing deposition temperature and reducing film thickness. This corresponds well with earlier results [36], where the alumina films delaminate from the substrate after reaching a critical thickness. Owing to an increased thickness, the stress near the interface increases, resulting in a lower fracture toughness of the film/substrate interface.…”
Section: Discussionsupporting
confidence: 93%
“…It was found before [29] that the films contain alumina and boehmite (AlO( OH)). X-Ray photoelectron spectroscopy measurements revealed that the amount of boehmite decreased with increasing temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Gases containing HCl for example, can influence the corrosion caused by other mechanisms, such as sulfidation, by breaking down the protective oxides and allowing corrosive species to reach the metal surface [18]. Similar results have been reported by Haanappel et al [19], who found that HCl in an oxidizing-sulfidizing environment increased the corrosion rate significantly and made the scales thick, porous and non-protective, comparable to the results of this study.…”
Section: Discussionsupporting
confidence: 81%
“…Cuando este fenómeno ocurre en ambientes oxidantes se le conoce como oxidación activa. Numerosos estudios han abordado la influencia de los gases Cl 2 (g) y HCl(g) en la corrosión a altas temperaturas de diferentes aleaciones [8][9][10][11][12][13][14][15][16] . Se acepta, generalmente, que las especies cloradas pueden producir una rotura de la capa de óxido protectora de la superficie.…”
Section: Corrosión Asociada a Especies Cloradas Gaseosasunclassified